Attenuation of lung injury using simvastatin in a rat sepsis model - Medeiros, Vítor Brasil; Azevedo, Ítalo Medeiros de; Rego, Amália Cínthia Meneses; Araújo-Filho, Irami; Carvalho, Marília Daniela Ferreira; Medeiros, Aldo Cunha (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2012)
Purpose: Considering that statins have pleiotrophic effects, we hypothesized that vimvastatin therapy could help in the setting of sepsis and lung injury. The aim of this study was to address the effect of simvastatin pretreatment on lung injury in rats with abdominal sepsis. Methods: Thirty male Wistar rats weighing 235±26g were used and distributed into the three groups: group 1, n=10 (sham), treated with oral injection of saline (10mL/Kg) 24 hs before and again immediately before surgery; group 2, n=10 (abdominal sepsis+saline), cecal ligation and puncture (CLP) and treatment with saline as group 1; group 3, n=10 (abdominal sepsis+simvastatin), CLP and treatment with oral injection (gavage) of 10mg/Kg of simvastatin suspension (10mg/ml) 24 hs before and again immediately before surgery. Commercial ELISA kits were used for measurement of tumor necrosis factor-alfa (TNF?), interleukin-1 (IL-1) and interleukin-6 (IL-6). Lung tissue from all animals was studied with light microscopy to determine the distribution and amount of lung injury. Results: TNF-? plasma expression was significantly lower in rats treated with simvastatin (172.8±25 pg/mL) than in rats treated with 0.9% saline (298.5±63 pg/ml). IL-1? plasma levels showed a drastic decrease (53.3±7 pg/mL) in simvastatin treated rats, compared with the sepsis/saline group rats (127.6±28 pg/mL). The plasma levels of IL-6 in the sepsis/simvastatin treated rats (53.3±7 pg/mL) were lower than in sepsis/saline treated rats (134.6±15mL). In control rats the plasma cytokines were significantly less expressive (28.4±6) than in the other groups. Representative lung histology demonstrated marked inflammation characterized by abundant interstitial neutrophils and edema in group sepsis/saline. Induced inflammation was greatly reduced by simvastatin pretreatment. Conclusion: In conclusion, our data suggest that simvastatin protects the lung against tissue injury in abdominal sepsis via inhibition of cytokines expression.